Long-term evaluation of NEDA-3 status in relapsing-remitting multiple sclerosis patients after switching from natalizumab to fingolimod. (August 2018) - Diem, Lara; Nedeltchev, Krassen; Kahles, Timo; Achtnichts, Lutz; Findling, Oliver
Background: Natalizumab significantly reduces the disease activity in patients with relapsing-remitting multiple sclerosis but due to the risk of progressive multifocal leukoencephalopathy it is often discontinued. Fingolimod is seen as an alternative, but there are no long-term analyses of the efficacy of fingolimod in this setting using the no evidence of disease activity (NEDA)-3 criteria. We provide an assessment of patients who discontinued natalizumab and switched to fingolimod or other treatments by evaluating the proportion of patients who fulfil NEDA-3 criteria after prolonged follow-up periods. Methods: We conducted a retrospective observational study of multiple sclerosis patients, who were treated with continuous natalizumab or who had switched to fingolimod or other treatments after natalizumab discontinuation. We assessed NEDA-3 status, annual relapse rate and determined the odds ratio between disease course after treatment switch and other patient and treatment characteristics. Results: A total of 61 patients on continuous natalizumab treatment and 53 patients who switched from natalizumab to fingolimod or other treatments were accompanied for up to 5 years. While the proportion of natalizumab patients fulfilling NEDA-3 criteria remained stable at 90% during the entire follow-up period, the proportion of patients switching to fingolimod or other therapies dropped to 76.7% in the first year after discontinuation, and to 50% in the years thereafter. While the median Expanded Disability Status Scale remained stable and the percentage of relapsing patients did not change significantly, recurring magnetic resonance imaging activity was found in up to 42% of the patients after switching from natalizumab to other treatments. New disease activity was significantly correlated with extended treatment gap between natalizumab discontinuation and the start of a new therapy. Discussion: Patients remain clinically stable after discontinuing natalizumab and switching to other therapies. However, when considering NEDA-3 criteria, a considerable proportion of patients show disease reactivation. Careful monitoring and early evaluation of alternatives is necessary after switching from natalizumab to other treatments.